Evaluation of Course Content of Mushroom Cultivation TechnologyTraining Programme for Farmers (Indian Journal of Extension Education, 2011)
The study was conducted to evaluate the course contents of the National Training Course on Mushroom Production Technology for farmers, farm women and unemployed youths with a view to make improvement in the training programme. The selected trainees were given one week training on cultivation technology of various types of mushrooms. The subject matter taught during the training was evaluated at the end. The results reveal that majority of the lectures (72.58%) and practicals (67.74%) were of high level usefulness and the rest were of medium level usefulness. None of the lecture belonged to low level of usefulness.